ENHANCED JOB SCHEDULING ALGORITHMS USING RESOURCE FORECASTS FOR VOLUNTEER GRID - RUBAB, SADDAF (2018)
Volunteer Grid (VG) computing provides a solution and makes use of idle resources that are spread around us, providing an estimate of one billion of computational power. The development and rise of volunteer grid has benefitted many scientific and industrial projects by serving computation of intensive jobs.